The influence of heat treatment on microstructure and wear properties of friction stir welded AA6061-T6/Al2O3 nanocomposite joint at four different traveling speed. (April 2016) - Farahmand Nikoo, M.; Azizi, H.; Parvin, N.; Yousefpour Naghibi, H.
Abstract: In the present study, 6 mm thick AA6061-T6 alloy was friction stir welded (FSWed) at different traveling speeds while Al2 O3 nano-particles were incorporated between adjoining plates. To investigate the influence of post weld heat treatment (PWHT) on microstructure and wear properties, solution treatment cycle was applied to FSWed specimens for 1 h at 540 °C then aged for 18 h at 180 °C. Distribution of Al2 O3 nano-particles in the stir zone (SZ) was observed via scanning electron microscopes (SEM). After heat treatment, grain size changed imperceptibly. Surprisingly, all specimens exhibited inferior hardness to the as-received AA6061-T6 alloy which was attributed to precipitates solution during FSW. After heat treatment, hardness value of the specimen FSWed at 40 mm/min improved. In the meantime, the uniform dispersion of Al2 O3 particles in this specimen resulted in refinement and homogenous distribution of strengthening precipitates. Thanks to Al2 O3 nano-particles, wear loss reduced remarkably (62%). Additionally, after heat treatment, the specimen FSWed at 40 mm/min showed improved wear behavior.